ESSENTIAL DRUG MANAGEMENT AT RSU KARSA HUSADA BATU: POLICY IMPLEMENTATION - Haksama, Setya (Journal of Indonesian Health Policy and Administration, 2020)
Coordination in a hospital is a necessary process needed to reach the organization’s goals. One of the processes that need coordination among cross-functional units is the essential drug procurement. The essential drug in Karsa Husada Batu Public Hospital (RSU Karsa Husada Batu) was often out of stock condition in some specific kinds of drugs. The average of the essential drug out of stock between the year of 2017 until the first semester of 2018 reached 33,73%. This number was far from the ideal standard of 0% out of stock condition. This research was aimed to recommend better coordination of essential drug management. The study used quantitative research and the data is collected using a questionnaire. The population in this research was all hospital staff who participate in essential drug procurement in RSU Karsa Husada Batu. There were 29 samples as the respondents in this research, which used purposive sampling, and the data collection took place in January until February 2019. The data is analyzed based on distribution analysis. Some communication aspects that has reached good results are intensity (69,00%), timing (65,50 %), accuracy (79,30%), and problem-solving (69,00%). However, mutual respect (58,60%), knowledge sharing (58,62%), and goal coordination (65,52%) had not reached the targeted result. Mutual respect and goal coordination should be the focus of hospital management to reach the goal of essential drug availability